The ethical questioning facing the stakes of the biotechnology - J., BASTOLO Bolaya; LOBWA Bosongo S.; D., NGIMA Libete; BONGILO Boendy J.F. (IJRDO-Journal of Applied Science, 2019)
In the setting of this survey, the major worry is to bring the scientists to understand that if the development of the science and the one of the technology constitutes an asset for the humanity, however, it stops generating ominous consequences at life, because the man remained the permanent target of this progress. Because the ethical questioning, for to protect the human of these increasing stakes. The new biotechnologies are susceptible to drag the humanity in the depersonnification, if they are not accompanied by the ethical mission, the genetically modified organisms, the pollution of the atmosphere, the genetic engineering of the living, the deterioration of the environment under the human pressure, the chemical weapons, the clonage on the animals and the plants, the procreation medically recipient of state aid, gas to additional greenhouse effect, must take place etc. under the eye vigilant of the moral conscience.